Analisis Pengaruh Permainan Bola Basket Dalam Mengurangi Berat Badan Berlebih - I Putu Agus Dharma Hita; Doni Pranata; Elsa Ariestika (Journal of Educational Innovation and Public Health, 2024)
This research investigates the influence of basketball game in reducing excess weight among children and adolescents through a literature review approach. By conducting an in-depth review of relevant literature, this study identifies the physical, psychological, and social benefits of basketball game in the context of weight management. The results of the analysis indicate that basketball game offers significant potential as one of the effective strategies in addressing obesity, by providing intensive physical activity, enhancing psychological well-being, and promoting teamwork and positive social relationships. However, challenges still exist in promoting participation in this game, particularly related to accessibility and support of adequate sports facilities. Therefore, collaborative efforts from various parties are needed to create an environment that supports and facilitates participation in basketball game as part of a sustainable active lifestyle.